2014
DOI: 10.3928/1081597x-20140320-05
|View full text |Cite
|
Sign up to set email alerts
|

Non-topography–guided Photorefractive Keratectomy for the Correction of Residual Mild Refractive Errors After ICRS Implantation and CXL in Keratoconus

Abstract: At the 6-month follow-up, non-topography-guided PRK after ICRS implantation and CXL was found to be an effective and safe option for correcting residual refractive error and improving visual acuity in patients with moderate keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…The procedure led to UDVA and CDVA improvement and a decrease of the steep Sim K from 50.37 D to 44.21 D, as well as reduction of corneal asymmetry and spherical aberration. Epithelial removal has also been attempted by use of excimer laser; either via lamellar phototherapeutic keratectomy (PTK) [24], topography guided [25], or noncustomized PRK [26]. In addition to gentle epithelial removal, all three options showed stabilizing CXL effect and certain visual improvements due to better corneal optics.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure led to UDVA and CDVA improvement and a decrease of the steep Sim K from 50.37 D to 44.21 D, as well as reduction of corneal asymmetry and spherical aberration. Epithelial removal has also been attempted by use of excimer laser; either via lamellar phototherapeutic keratectomy (PTK) [24], topography guided [25], or noncustomized PRK [26]. In addition to gentle epithelial removal, all three options showed stabilizing CXL effect and certain visual improvements due to better corneal optics.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] The impact of CXL combined with TG-PRK in patients' selfreported quality of life has been reported previously using various validated tools. 9,12,23 Labiris et al, 13 in a controlled study, reported that CXL combined with TG-PRK offered an improved self-reported quality of life in patients after treatment, but the scores of the patients with keratoconus were significantly lower than those of the matched healthy controls. The authors concluded that the technique should be implemented as soon as possible for the treatment of keratoconus.…”
Section: Discussionmentioning
confidence: 99%
“…The Ocular Wavefront Analyser and the Corneal Wavefront Analyser are reliable and have been recommended for use in refractive surgery, even though the Hartmann-Shack device was favored. 28 Although studies [12][13][14][15][16][18][19][20][21]23,34,35 have shown similar significant improvements in most of the tested visual functions, they have been conducted on a different population sample and/or have not agreed on all findings, partly because of the variation in the surgical protocol, and data collection/analysis method or follow-up duration. Additionally, many of these studies have been performed on a few eyes 15,16,20,21,23 and have used a format which is different from that recommended 25,26 in presenting their graphic data, thus making it difficult to directly compare results between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 3-stage procedure has been proposed to halt the ectatic process, improve the corneal shape and visual acuity, and minimize the residual refractive error. Five studies analysed the efficacy and safety of the triple procedure: corneal CXL, ICRS implantation, and PRK [ 123 132 ]. All of these studies reported significant improvement in visual acuity, refraction, and corneal shape.…”
Section: Combined Proceduresmentioning
confidence: 99%